Narrative Medicine: theory, clinical practice and education - a scoping review - Ilaria Palla; Giuseppe Turchetti; Stefania Polvani (BMC, 2024)
Abstract Background The origin of Narrative Medicine dates back to more than 20 years ago at an international level. Narrative Medicine is not an alternative to evidence-based medicine, however these two approaches are integrated. Narrative Medicine is a methodology based on specific communication skills where storytelling is a fundamental tool to acquire, understand and integrate several points of view related to persons involving in the disease and in the healthcare process. Narrative Medicine, henceforth NM, represents a union between disease and illness between the doctor's clinical knowledge and the patient's experience. According to Byron Good, "we cannot have direct access to the experience of others' illness, not even through in-depth investigations: one of the ways in which we can learn more from the experience of others is to listen to the stories of what has happened to other people." Several studies have been published on NM; however, to the best of our knowledge, no scoping review of the literature has been performed. Objective This paper aims to map and synthetize studies on NM according to theory, clinical practice and education/training. Method The scoping review was carried out in accordance with the Preferred Reporting Items for Systematic Reviews and Meta-Analyses extension for scoping reviews (PRISMA-ScR) checklist. A search was conducted in PubMed, APA PsycNet and Jstor. Two authors independently assessed the eligibility and methodological quality of the studies and extracted the data. This review refers to the period from 1998 to 2022. Results A total of 843 abstracts were identified of which 274 papers were selected based on the title/abstract. A total of 152 papers in full text were evaluated and 76 were included in the review. Papers were classified according to three issues: ✘ Nineteen studies focused on the definition and concept of NM (Theoretical). ✘ Thirty-eight papers focused on the collection of stories, projects and case reports (Clinical practice). ✘ Nineteen papers focused on the implementation of the Narrative Medicine approach in the education and training of medical doctors (Education and training). Conclusions This scoping review presents an overview of the state of the art of the Narrative Medicine. It collect studies performed mainly in Italy and in the United States as these are the countries developing the Narrative Medicine approach in three identified areas, theoretical, clinical practice and education and training. This scoping review will help to promote the power of Narrative Medicine in all three areas supporting the development of methods to evaluate and to measure the Narrative Medicine approach using key performance indicators.